Phenotype and genotype characteristics of Indonesian 21-hydroxylase deficient patients - Atiek Widya Oswari; Bambang Tridjaja; Iswari Setianingsih; Taralan Tambunan; Aman B. Pulungan; Jose R. L. Batubara (Paediatrica Indonesiana, 2007)
Background Congenital adrenal hyperplasia (CAH) is the mostcommon cause of ambiguous genitalia in children and 90-95%cases show 21-hydroxylase deficiency. More than 100 mutationshave been described and of these, four mutations have beenfrequently reported in Asia. Those mutations are deletion/largegene conversion (LGC), intron2 splice mutation (I2 splice), pointmutations at codon 172 (I172N) and codon 356 (R356W).Genotyping is very valuable since close correlation observedbetween genotype and phenotype.Objective To identify phenotype and genotype characteristics ofCAH due to 21-hydroxylase deficiency (CAH-21OH) andcorrelation between them.Methods From June to November 2006 we analyzed 37 confirmedCAH-21OH patients treated at the Department of Child Health,Cipto Mangunkusumo Hospital during the period of 1990-2006.Polymerase chain reaction (PCR) followed by restriction fragmentlength polymorphism (RFLP) analysis or amplification-createdrestriction site (ACRS) were performed. We first identified deletion/LGC and I172N mutation that had been mostly reported in saltwasting (SW) and simple virilizing (SV) form patients respectively.Results There were 37 patients, consisted of 6 males and 31females with the ratio 1:5.2. Of those, 25, 10, 2 patients wereSW, SV and non-classic (NC) form, respectively. PCR-RFLP orACRS was performed to detect two mutations in 32 patients (64alleles). Deletion/LGC was found in 6 alleles while I172Nmutations in two. All deletion alleles showed SW phenotype butI172 mutated alleles showed SW and SV phenotype.Conclusion There is a consistent close association betweengenotype and phenotype in our CAH-21OH patients.